2022
DOI: 10.1002/rcm.9405
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic, dual amino acid–functionalized zinc sulfide quantum dot for specific identification of N‐glycopeptides from biological samples

Abstract: translational modifications, and N-glycosylation plays a crucial role in life activities.Mass spectrometry (MS) has been a powerful technique in the analysis of protein glycosylation. However, the direct detection of glycoproteins in biological samples based on MS still suffers from huge challenges. Therefore, enrichment and purification of samples before MS analysis is an essential prerequisite.Methods: Hydrophilic interaction liquid chromatography (HILIC) has significantly developed for selective enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In a previous study, we observed that the absorbance maxima were changed very slowly for MB without the use of ZnS on sunlight illumination. 16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we observed that the absorbance maxima were changed very slowly for MB without the use of ZnS on sunlight illumination. 16 …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we observed that the absorbance maxima were changed very slowly for MB without the use of ZnS on sunlight illumination. 16 Such data indicates the efficient photocatalytic ability of ZnS under sunlight exposure. Further, under the same experimental conditions, L-GA/ZnS composites were employed as photocatalysts to evaluate their photocatalytic performance with that of L-GA alone.…”
Section: Photocatalytic Performancementioning
confidence: 94%
See 2 more Smart Citations